Manifestations of the African Renaissance in Contemporary South African Literature and Art - (:unkn) unknown (My University, 2023)
The concept of an “African Renaissance”, to be led by South Africa, entered the political arena following Thabo Mbeki’s “I am an African” speech, made at the adoption of South Africa’s new Constitution in 1996. It became particularly popular during Mbeki’s presidency (1999-2008). This paper will examine humorous portrayals of so-called African Renaissance men and women in a few examples of South African literature and visual arts.
Keywords: African Research